2019
DOI: 10.4149/neo_2018_180420n253
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of ultrasonic features with severity of liver cancer and p16 expression in patients with liver cancer

Abstract: This paper analyzes the correlations of ultrasonic features with clinical-pathological manifestations and p16 expression in patients with liver cancer. A total of 84 patients with primary liver cancer were randomly enrolled. The characteristics of liver cancer were examined via conventional ultrasound and contrast-enhanced ultrasound (CEUS) before operation. The p16 protein expressions in liver cancer and para-carcinoma tissues were detected via immunohistochemistry (IHC), and the correlations of p16 positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Color ultrasound enables the screening of liver cancer lesions, determining the presence or absence of a tumor, and analysis of the nature and composition of a tumor. In addition, CDFI enables the monitoring of blood flow inside a lesion and its surroundings, obtaining the related information, etc., allowing for a qualitative diagnosis of the lesion based on the hemodynamic characteristics [15]. Contrast-enhanced ultrasonography (CEUS) enables the early detection of vascular lesions within a tumor.…”
Section: Diagnosis and Treatment Of Liver Cancer 21 Imaging Diagnosis...mentioning
confidence: 99%
“…Color ultrasound enables the screening of liver cancer lesions, determining the presence or absence of a tumor, and analysis of the nature and composition of a tumor. In addition, CDFI enables the monitoring of blood flow inside a lesion and its surroundings, obtaining the related information, etc., allowing for a qualitative diagnosis of the lesion based on the hemodynamic characteristics [15]. Contrast-enhanced ultrasonography (CEUS) enables the early detection of vascular lesions within a tumor.…”
Section: Diagnosis and Treatment Of Liver Cancer 21 Imaging Diagnosis...mentioning
confidence: 99%
“…But while it has been reported sensitive in detection of even asymptomatic tumors, factors like doubling time of the lesion and experience of the clinician in interpretation of the scan are critical for success. Different meta-analytic studies suggest that a combination of USG findings with clinico-pathological manifestations and other biomarkers, like p16 expression and serum alpha-fetoprotein (AFP), can have greater sensitivity for early-stage HCC than USG alone [21,22]. In a retrospective analysis involving [ 250 patients, Schwarze et al showed that contrast-enhanced USG demonstrated remarkable accuracy compared to MRI as a diagnostic gold standard [23].…”
Section: Ultrasonographymentioning
confidence: 99%
“…Among them, ultrasound and CT are used usually, but conventional ultrasound has some limitations, such as conventional CT with a longer scanning time. In addition, the advantage of contrast-enhanced ultrasound examination is that it can effectively improve the diagnosis sensitivity and specificity of PHC by real-time observation of blood perfusion in hepatic tissues, while enhanced CT is a focused examination after injection of radiography agent into suspect area on the basis of plain scan [7][8][9]. However, the international guidelines recommend enhanced CTas the first-line method of imaging examination for PHC at present, while contrast-enhanced ultrasound is only used as a second-line inspection means, with a controversy in diagnostic value.…”
Section: Introductionmentioning
confidence: 99%